1988
DOI: 10.3758/bf03334846
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of retrieving information from knowledge structures in memory: Scripts

Abstract: Research has shown that the reliability of retrieving information from knowledge structures in memory is surprisingly low. For many knowledge structures only about half the information retrieved in one session is the same information retrieved in a second session 1 week later. A number of theorists have argued that knowledge structures known as scripts are particularly important and well-organized knowledge structures. The purpose of the two experiments reported here was to determine the reliability of retriev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 12 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…He found that only 69% of the exemplars retrieved in the first session were retrieved again 1 week later. Retrieval reliability is even lower for noun meanings, facts about people, and scripts (Bellezza, 1984b(Bellezza, , 1984c(Bellezza, , 1988. Perhaps most surprisingly, retrieval reliability of information about the self, thought to be better organized and more salient than information about other knowledge domains (e.g., Epstein, 1973;Greenwald, 1981;Kuiper & Rogers, 1979), is in fact even lower (51%) than the retrieval reliability for common taxonomic categories such as fruit and fish (76%; Bellezza, 1987; see also Greenwald, Bellezza, & Banaji, 1988).…”
Section: The Malleability Of Conceptual Knowledgementioning
confidence: 95%
“…He found that only 69% of the exemplars retrieved in the first session were retrieved again 1 week later. Retrieval reliability is even lower for noun meanings, facts about people, and scripts (Bellezza, 1984b(Bellezza, , 1984c(Bellezza, , 1988. Perhaps most surprisingly, retrieval reliability of information about the self, thought to be better organized and more salient than information about other knowledge domains (e.g., Epstein, 1973;Greenwald, 1981;Kuiper & Rogers, 1979), is in fact even lower (51%) than the retrieval reliability for common taxonomic categories such as fruit and fish (76%; Bellezza, 1987; see also Greenwald, Bellezza, & Banaji, 1988).…”
Section: The Malleability Of Conceptual Knowledgementioning
confidence: 95%